There is no shortage, but inequality: demographic evolution of neurologists in Brazil (2010–2020) - Bruno Lopes Santos-Lobato; Pedro José Tomaselli; Edienny Augusta Viana Santos-Lobato; Alex Jones Flores Cassenote; Hideraldo Luis Souza Cabeça (Arquivos de Neuro-Psiquiatria)
Background Neurology is a medical specialty that deals with prevalent diseases such as stroke, headache, epilepsy, and neurodegenerative diseases. Many countries, such as Brazil, struggle to provide neurological care for their populations, but the inadequacy and unequal distribution of the neurologist workforce are real challenges. Objective To analyze the demographic evolution of neurologists and the first-year Neurology residency positions in Brazil during the last decade (2010–2020) and the distribution imbalance between regions. Methods The demographic and geographic distribution of neurologists was calculated based on data extracted from the Brazilian Federal Medical Council reports, and the number of Neurology residency positions was based on the Brazilian National Commission of Medical Residency reports. Indicators of wealth were associated with demographic data. Results The number of neurologists per 100,000 population has increased since 2011, with a similar increase in the geographic distribution of neurologists. However, there was a marked inequality of distribution of neurologists through regions, with a gap between the Northern (lowest) and Southeastern (highest) regions. Furthermore, the imbalance of distribution of neurologists strongly correlated with social inequality. The number of Neurology residency positions increased, but with an imbalance between North and Southeast regions. Conclusions Brazil has advanced in providing neurologists. However, instead of a shortage, inequality between regions is the greatest challenge regarding the neurological workforce. The training of new neurologists is unequal between regions and occurs at a slower rate than needed. Neurologists, public health authorities, and patients should discuss solutions for these issues.